Numerical Solutions of the Aligned Magnetic Field on the Boundary Layer Flow and Heat Transfer over a Stretching Sheet by using Keller-box Method - Nur Syamilah, Arifin; Syazwani, Mohd Zokri; Abdul Rahman, Mohd Kasim; Mohd Zuki, Salleh; Nurul Farhain, Mohammad (Universiti Malaysia Pahang, 2016)
In this study, the influence of aligned magnetic field on the steady boundary layer flow and heat transfer over a stretching sheet together with Newtonian heating is considered. The transformed governing nonlinear boundary layer equations in the form of ordinary differential equations are solved numerically by Keller-box method. The numerical solutions of the applied magnetic field with different values of aligned angle, D1 on the velocity and temperature profile are presented graphically. It is found that, increases in aligned angle retarded the value of fluid’s velocity and increases the value of fluid’s temperature.